2011
DOI: 10.1007/s10646-011-0814-y
|View full text |Cite
|
Sign up to set email alerts
|

Cross-effects of nickel contamination and parasitism on zebra mussel physiology

Abstract: Aquatic organisms are exposed to pollution which may make them more susceptible to infections and diseases. The present investigation evaluated effects of nickel contamination and parasitism (ciliates Ophryoglena spp. and intracellular bacteria Rickettsiales-like organisms), alone and in combination, on biological responses of the zebra mussel Dreissena polymorpha, and also the infestation abilities of parasites, under laboratory controlled conditions. Results showed that after 48 h, more organisms were infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Hemocyte viability, phagocytosis, ROS production, lysosomal system size and CSP-3 induction were measured by flow-cytometry (FACScaliburTM, BD Biosciences) using protocols adapted from Minguez et al (2012).…”
Section: Biomarker Measurements -Detailed Protocols In Smmentioning
confidence: 99%
“…Hemocyte viability, phagocytosis, ROS production, lysosomal system size and CSP-3 induction were measured by flow-cytometry (FACScaliburTM, BD Biosciences) using protocols adapted from Minguez et al (2012).…”
Section: Biomarker Measurements -Detailed Protocols In Smmentioning
confidence: 99%
“…Ciliates were observed between the interfilamentar spaces of the current work without obvious effects. The presence of microorganisms in the gills of the clams collected from the polluted area was reported in several studies (Neff et al 1987;Minguez et al, 2012;Carella et al, 2016). They discussed that pollution could compromise the animals` defence system and make it susceptible to parasites and invading organisms.…”
Section: Discussionmentioning
confidence: 96%
“…This process has been well studied for vertebrate hosts (reviewed in [17]) and only a few publications focused on molluscs, essentially gastropods and marine bivalves ([35], [36] and reviewed in [1]). On D. polymorpha , our team has worked on the physiological modifications linked with parasitism in a context of environmental disturbances [29], [30], [31], [32]. Nonetheless, to better understand the system zebra mussel - its parasites, it seemed interesting to have a more mechanistic approach of the host-parasite relationship, for example, by focusing on apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…in the digestive gland, and extracellular cysts of trematodes Phyllodistomum folium in gills and Bucephalus polymorphus in gonads. Our previous studies have shown that these parasites induced some physiological disturbances more or less important for their host [29], [30], [31], [32]. However, to better understand these host-parasite systems, it is important to go into the finer mechanisms underlying the establishment of the parasite.…”
Section: Introductionmentioning
confidence: 99%